The interpreter - Abtahi, Olivia (Kokila, an imprint of Penguin Random House, 2025)
"Some kids have one job: to be a kid! Cecilia has two. When she isn't on the soccer field scoring goals, she's accompanying her parents to all kinds of grown-up places, like the DMV, the accountant's office, and the auto shop. She helps them translate from Spanish to English and from English to Spanish. It's an important job, and it can even be fun. It's also hard work. Sometimes Cecilia's second job is so much responsibility, it feels like she'll split in two! Is it time for Cecilia to blow her whistle and call for a time-out?"--